Contribution of HIV-1 subtype C envelope glycoprotein conformations in apoptosis of uninfected bystander CD4+ T lymphocytes - Manamela, Nelia Phuti (My University, 2019)
HIV-1 primarily infects CD4-expressing T lymphocytes causing their progressive depletion, ultimately leading to acquired immunodeficiency syndrome (AIDS). Interestingly, uninfected bystander CD4+ T cells are also implicated in the depletion. This bystander effect is attributed to the interaction of uninfected CD4+ T cells with viral proteins such as the envelope glycoproteins (Env) leading to programmed cell death commonly known as apoptosis. However, HIV-1 Env is dynamic and exists in monomeric and trimeric conformations, but the contribution of each conformation to bystander apoptosis remains controversial. Therefore this study evaluated the contribution of HIV-1 subtype C Env conformations to bystander apoptosis, specifically mediated via CD4 signalling. The Env conformations used included matched monomeric gp120FVC, trimeric gp140GCN4 and gp140SOSIP (based on founder virus sequence). Env recombinant proteins were expressed in HEK 293T and HEK 293F cells, as confirmed by SDS-PAGE and Western blots analyses. Subsequently, Env monomers and trimers were purified to homogeneity by lectin affinity and size exclusion chromatography, which were further confirmed by blue native PAGE. Structural integrity and functionality of each Env conformation was then validated using conformation-specific antibodies (CAP256-VRC26.25, 10E8, IgG1b12) and binding to antibody 17b in the presence of soluble CD4 in ELISAs, respectively. Bystander apoptosis induction of Jurkat T cells was measured by flow cytometry up to 72 hours post addition of a range (50 to 500 nM) of each functional Env conformation, using Annexin V/7-AAD stain, Mitopotential dye, Caspase 3/7 activation antibodies and Multicolor DNA damage assays. Overall, the trimeric gp140SOSIP and gp140GCN4 induced bystander apoptosis via mitochondrial membrane depolarization (intrinsic pathway) with onset reversible DNA fragmentation, in the absence of caspase 3/7 activation. Interestingly, only apoptosis induction by gp140GCN4 was associated with phosphatidylserine translocation. By contrast, the monomeric gp120FVC induced bystander apoptosis via both mitochondrial membrane depolarization (intrinsic pathway) and caspase 3/7 activation (extrinsic pathway) with low levels of phosphatidylserine translocation and negligible DNA fragmentation. Collectively, these results confirmed the ability of both vi monomeric and trimeric Env conformations to induce CD4-mediated bystander apoptosis via varied mechanisms. The observed differences in apoptosis-inducing capacity of monomeric and trimeric Envs imply possible variations in CD4 binding affinities and signal activation, and warrant further investigation.
A dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science in Medicine, November 2019